Efeitos da substituição parcial de cacau por alfarroba em bebidas lácteas - Cassanego, Daniela Buzatti (2013)
The whey has been gaining ground and importance in the food industry. The milk beverages are one way to use this coproduct, the ones with chocolate flavor has broad consumer acceptance of both sexes and various ages. Carob is being studied as a possible replacement for cocoa by presenting color, odour and taste similar to cocoa, have lower production costs and does not contain caffeine and theobromine, substances known as antinutritional factors of cocoa. Given these facts, it was aimed to the development of milk beverages with the use of whey powder and partial replacement of cocoa for carob. The results showed that the use of 15% of whey powder added nutritional value and obtained the highest preference in the sensorial analysis, the use carob as a substitute for cocoa do not interfere in the physicalchemical analyzes of milk beverages. Were prepared 12 formulations of milk beverages with different concentrations of cocoa and carob powder, and analysis microbiological, sensory and physicochemical were performed. The counts of micro-organisms remained within the required by Brazilian law, the acceptability of sensory analysis revealed that higher levels of cocoa and carob added to milk beverages, increase the acceptance of evaluative attributes (color, odour, flavor and viscosity) the milk drink with higher level of carob powder was preferred over the other milk beverages. There were no statistical differences (p> 0.05) on the parameters of fat, moisture, protein and reducing sugars, the milk beverages had shelf life of 14 days. Considering these results it can be concluded that the partial replacement of cocoa for carob in milk beverages is an attractive alternative, since the samples were well accepted sensorially, had good intentions to purchase and there were no losses in nutritional formulations of milk beverages.